Pengaruh Pemberian Berbagai Jenis Pupuk Dasar Terhadap Pertumbuhan dan Hasil Cabai (Capsicum Annum L) - Nike Karjunita; Kuswandi Kuswandi (Jurnal Pembangunan Nagari, 2021)
Chili is one of the most widely cultivated vegetable commodities in Indonesia. Objective of the study was to determine the type of basic fertilizer that was best for the growth and yield of chili plants. The research was conducted from January to June 2019 in Nagari Pariangan, Pariangan District Tanah Datar Regency. The experiment was arranged according to the rules of Randomized Block Design (RAK) with 4 treatments and 3 replications, and each replication consisted of 3 samples. The treatments given were straw compost (A), cow manure (B), chicken manure (C), and artificial fertilizer (D). The observed variables consisted of plant height, number of dichotomous branches, flowering age, harvest age, fruit weight, number of fruit, and fruit weight per bed. Data were analyzed using F test at a 5% significance level. If the calculated F is greater than the F table, it is continued with a HSD test. Basic fertilizer with chicken manure provided the best growth and yield for chili plants, especially in the number of dichotomous branches, which was 67 pieces, the fastest flowering age was at 45 days after planting, the fastest harvest age was 91 days after planting, yielding fruit weight the heaviest per plant, that is, 49.96 g, the most number of fruits, which is 16.7 pieces and the highest yield per bed, which is 749.35 g. Recommendations in future research should be more focused on the application dose of basic chicken manure fertilizer so that it can be applied in more detail on farmers' land.